Legal responses to employment discrimination on the basis of psychosocial disabilities: Kenya’s and South Africa’s compliance with the convention on the rights of persons with disabilities - Genga, Shirley Anne Awuor (My University, 2022)
This thesis investigates whether Kenya and South Africa, as states parties to the CRPD, comply with its employment antidiscrimination provision which is enshrined in Article 27(1)(a). It focuses on the legal responses afforded to employees with psychosocial disabilities at CRPD level, as well as in the two domestic systems studied. Existing literature in Africa and further afield has mostly focused on employment discrimination against people with disabilities in general terms and not many studies have been comparative in nature. This research seeks to contribute to the development of laws that seek to prohibit and otherwise address discrimination against persons with psychosocial disabilities. It does so by critically analysing the CRPD antidiscrimination provisions and by then examining how two African countries have fared in complying with these aspects of the CRPD. This research relies on the social model of disability as lenses through which to engage critically with the antidiscrimination laws in both states and at CRPD level. It engages critically with the national Constitutions, legislation and case law of Kenya and South Africa. It also considers and reflects on commentaries from law and other disciplines in the social sciences, including sociology, psychology and disability studies. The text of the CRPD, its preparatory documents, General Comments by the CRPD committee applications and decisions by the CRPD Committee are also analysed. It is concluded that the laws in both Kenya and South Africa are based on medicalised, individual approaches to disability. These approaches not only affect who qualifies for protection from discrimination on the basis of disability, but filter through to aspects such as whether discrimination can be proven, the scope, application, and even the enforcement of antidiscrimination laws in both states. It is concluded that both Kenya and South Africa could improve the working definitions of disability adopted and applied, particularly in the context of psychosocial conditions. Both countries could also improve employees’ access to expeditious, accessible forums. Furthermore, both jurisdictions, as well as the CRPD, could provide more guidance on the standard of proof complainants have to meet in order to prove discrimination. Kenyan law is unnecessarily restrictive in its requirements that only persons with disabilities who are registered may qualify as disabled for antidiscrimination purpose. In addition, Kenya also has to clarify the place of harassment and reasonable accommodation within its antidiscrimination framework. Finally, Kenyan legislation could expand the remedies courts are empowered to award, particularly to combat structural discrimination in employment policies and practices. South African law has to provide more clarity on the approach to discrimination on the basis of association with persons with psychosocial disabilities or conditions. While Kenya and South Africa have to address shortcomings and can improve their compliance with the CRPD in protecting persons with psychosocial disabilities or conditions from discrimination in employment, both jurisdictions have solid bases to work from in their respective Constitutions. Positive developments in mental health policy and access to mental health care are also crucial to employment outcomes.
This thesis is presented in partial fulfilment for the Degree of Doctor of Philosophy in Law to the Faculty of Commerce, Law, and Management, University of the Witwatersrand, 2021